2013
DOI: 10.1074/jbc.m113.458661
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous APOBEC3A DNA Cytosine Deaminase Is Cytoplasmic and Nongenotoxic

Abstract: Background: APOBEC3A is a potentially genotoxic DNA cytosine deaminase expressed in myeloid lineage cells. Results: Exogenous APOBEC3A genotoxicity correlates with expression level and nuclear localization. Endogenous APOBEC3A is nontoxic and cytoplasmic, despite its capacity to be highly induced by interferon. Conclusion: Cytoplasmic localization prevents endogenous APOBEC3A from accessing nuclear DNA. Significance: Endogenous APOBEC3A is not genotoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 55 publications
9
81
0
Order By: Relevance
“…This issue has been addressed recently in the study of endogenous A3A localization in monocytes; a cell type with high endogenous A3A expression. In monocytes it appears there is a mechanism absent from other cell types that keeps A3A in the cytoplasm and prevents it from damaging the genome [55]. Different polymorphisms in A3H have been shown to alter its subcellular localization, which suggests the affected amino acids play a role in blocking the passive diffusion of this enzyme between cytoplasm and nucleus [56].…”
Section: A3 Expression and Stimulationmentioning
confidence: 99%
“…This issue has been addressed recently in the study of endogenous A3A localization in monocytes; a cell type with high endogenous A3A expression. In monocytes it appears there is a mechanism absent from other cell types that keeps A3A in the cytoplasm and prevents it from damaging the genome [55]. Different polymorphisms in A3H have been shown to alter its subcellular localization, which suggests the affected amino acids play a role in blocking the passive diffusion of this enzyme between cytoplasm and nucleus [56].…”
Section: A3 Expression and Stimulationmentioning
confidence: 99%
“…[2,3,[9][10][11]14,46] An argument has been presented that an APOBEC3A/B mutation pattern persists even in cancer samples that harbor the APOBEC3B deletion allele. [58] This, were it the case, would imply that the signature is likely the result of APOBEC3A since APOBEC3B is absent in the cells homozygous for the APOBEC3B deletion.…”
Section: An Apobec3b Deletion Alellementioning
confidence: 99%
“…APOBEC3B is the only family member that constitutively localizes to the cell nucleus. [9,45,46] Also, it retains deamination activity, increases the steady-state level of uracil in the cell's genome, and correlates with increased mutation, as determined by selection and enrichment techniques (thymidine kinase (TK)-fluctuation assay and 3D-PCR/sequencing). [9] These findings indicated that in a large proportion of breast cancer cell lines, APOBEC3B is driving mutations that diversify the genetic landscape.…”
Section: Apobec3b and Breast Cancermentioning
confidence: 99%
“…Apo3A when overexpressed can be cytotoxic by inducing strand breaks in genomic DNA that activate damage response causing cell-cycle arrest (17, 18, 29 -31). It has recently been reported that endogenous Apo3A can be prevented from entering nuclei, but a mechanism has not been identified (18). If entry into nuclei does occur, then to protect against potential inadvertent action of Apo3A, an interaction between the TRIB3 protein and Apo3A prevents deamination of genomic DNA, promotes enzyme degradation, thereby eliminating cytotoxicity (17).…”
mentioning
confidence: 99%
“…Apo3A functions not just in the cytoplasm of myeloid cells, but when overexpressed in a variety of cultured cells it mutates nuclear and mitochondrial DNA (17)(18)(19)(20). Although Apo3A acts against HIV-1 in its natural myeloid cellular setting, its overexpression inhibits replication of many viruses including papilloma (21), adenoassociated (13,22), Rous sarcoma (23), T-lymphotropic type 1 (24), degrades foreign DNA (25), and blocks retrotransposition of LINE-1, Alu, and TLR (13, 26 -28).…”
mentioning
confidence: 99%